Dysbiotic oral microbiota and infected salivary glands in Sjögren’s syndrome - Alam, Jehan; Lee, Ahreum; Lee, Junho; Kwon, Dong Il; Park, Hee Kyung; Park, Jung-Hyun; Jeon, Sumin; Baek, Keumjin; Lee, Jennifer; Park, Sung-Hwan; Choi, Youngnim (PloS one, 2020)
Key events in the pathogenesis of Sjӧgren syndrome (SS) include the change of salivary gland epithelial cells into antigen-presenting cell-like phenotypes and focal lymphocytic sialadenitis (FLS). However, what triggers these features in SS is unknown. Dysbiosis of the gut and oral microbiomes is a potential environmental factor in SS, but its connection to the etiopathogenesis of SS remains unclear. This study aimed to characterize the oral microbiota in SS and to investigate its potential role in the pathogenesis of SS. Oral bacterial communities were collected by whole mouthwash from control subjects (14 without oral dryness and 11 with dryness) and primary SS patients (8 without oral dryness and 17 with dryness) and were analyzed by pyrosequencing. The SS oral microbiota was characterized by an increased bacterial load and Shannon diversity. Through comparisons of control and SS in combined samples and then separately in non-dry and dry conditions, SS-associated taxa independent of dryness were identified. Three SS-associated species and 2 control species were selected and used to challenge human submandibular gland tumor (HSG) cells. Among the selected SS-associated bacterial species, Prevotella melaninogenica uniquely upregulated the expression of MHC molecules, CD80, and IFNλ in HSG cells. Concomitantly, P. melaninogenica efficiently invaded HSG cells. Sections of labial salivary gland (LSG) biopsies from 8 non-SS subjects and 15 SS patients were subjected to in situ hybridization using universal and P. melaninogenica-specific probes. Ductal cells and the areas of infiltration were heavily infected with bacteria in the LSGs with FLS. Collectively, dysbiotic oral microbiota may initiate the deregulation of SGECs and the IFN signature through bacterial invasion into ductal cells. These findings may provide new insights into the etiopathogenesis of SS.